Neonatal-onset mitochondrial disease: clinical features, molecular diagnosis and prognosis. Issue 3 (7th October 2021) - Ebihara, Tomohiro; Nagatomo, Taro; Sugiyama, Yohei; Tsuruoka, Tomoko; Osone, Yoshiteru; Shimura, Masaru; Tajika, Makiko; Matsuhashi, Tetsuro; Ichimoto, Keiko; Matsunaga, Ayako; Akiyama, Nana; Ogawa-Tominaga, Minako; et al.
Abstract : Objective: Neonatal-onset mitochondrial disease has not been fully characterised owing to its heterogeneity. We analysed neonatal-onset mitochondrial disease in Japan to clarify its clinical features, molecular diagnosis and prognosis. Design: Retrospective observational study from January 2004 to March 2020. Setting: Population based. Patients: Patients (281) with neonatal-onset mitochondrial disease diagnosed by biochemical and genetic approaches. Interventions: None. Main outcome measures: Disease types, initial symptoms, biochemical findings, molecular diagnosis and prognosis. Results: Of the 281 patients, multisystem mitochondrial disease was found in 194, Leigh syndrome in 26, cardiomyopathy in 38 and hepatopathy in 23 patients. Of the 321 initial symptoms, 236 occurred within 2 days of birth. Using biochemical approaches, 182 patients were diagnosed by mitochondrial respiratory chain enzyme activity rate and 89 by oxygen consumption rate. The remaining 10 patients were diagnosed using a genetic approach. Genetic analysis revealed 69 patients had nuclear DNA variants in 36 genes, 11 of 15 patients had mitochondrial DNA variants in five genes and four patients had single large deletion. The Cox proportional hazards regression analysis showed the effects of Leigh syndrome (HR=0.15, 95% CI 0.04 to 0.63, p=0.010) and molecular diagnosis (HR=1.87, 95% CI 1.18 to 2.96, p=0.008) on survival. Conclusions: Neonatal-onset mitochondrial disease has a heterogenous aetiology. The number of diagnoses can be increased, and clarity regarding prognosis can be achieved by comprehensive biochemical and molecular analyses using appropriate tissue samples. Abstract : The authors analyzed neonatal-onset mitochondrial disease in Japan via a retrospective observational study to clarify its clinical features, molecular diagnosis, and prognosis. The heterogeneous aetiology if the group is outlined.